Restauração transcirúrgica como alternativa na resolução das perfurações endodônticas - Ribeiro, Clicia Pereira [UNESP]; Santos, Regiane dos; Oliveira e Silva, Cleverson de; Marson, Fabiano Carlos; Facundo, Aguinaldo Cândido da Silva [UNESP]; Gomes Filho, João Eduardo [UNESP]; Dezan Junior, Eloi [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (My University, 2013)
The endodontic perforations are iatrogenic communications that result in a communication between the endodonto and periodontium. This occurrence represents about 10 % of cas- es of failure in endodontic treatment. The management may vary and is related to the drilling site endodontic. This paper aims to report a case of iatrogenic perforation and one of the possible alternatives for the treatment of endodontic perforations -level cervical tooth. During the opening coronary perforation occurred due to improper slope cervical penetration drill. Considering the drilling site, we opted for sealing com- posite resin after surgical access and absolute isolation. After sealing, the channel was filled with medication and instru- mented based on calcium hydroxide. Later the canal was obturated by lateral condensation technique with Sealapex. The radiographic follow-up showed regression of the lesion and the clinical silence confirmed the success of the treatment.

As perfurações endodônticas são comunicações iatrogênicas que resultam em uma comunicação entre o endodonto e o periodonto. Esta ocorrência representa cerca de 10% dos casos de insucessos nos tratamentos endodônticos. A con- duta terapêutica pode variar e está relacionada com o local da perfuração endodôntica. O presente trabalho se propõe a relatar um caso de perfuração iatrogênica e uma das alternativas possíveis para o tratamento das perfurações endodônticas em nível de colo dentário. Durante a abertura coronária ocorreu perfuração cervical devido à incorreta inclinação de penetração da broca. Considerando o local da perfuração, optou-se pelo selamento com resina composta, após acesso cirúrgico e isolamento absoluto. Após o sela- mento, o canal foi instrumentado e preenchido com medicação à base de hidróxido de cálcio. Posteriormente o canal foi obturado pela técnica da condensação lateral ativa com cimento Sealapex. O acompanhamento radiográfico mostrou regressão da lesão e o silêncio clínico confirmou o su- cesso do tratamento.
Trans surgical restoration as an alternative to resolution of perforations endodontic
Keywords: Endodontic perforations; Sealing; Perfurações endodônticas; Selamento